Oxygen Saturation During Dental Surgery with Local Anesthesia Alone and in Combination with Sedation in Medically Compromised Patients - Mohamed Hilal; Nasradeen Ajanan (Khalij-Libya Journal of Dental and Medical Research, 2022)
Objective. The aim of this study was to determine which specific operative events are associated with change in SaO2 and blood pressure and heart rate in patients undergoing exodontia or minor oral surgery with local anaesthetic Medically compromised patients with Local anaesthesia alone or in combination with sedation. Methods. Arterial oxygen saturation (SaO2) with Heart rate and blood pressure was measured in 60 patients divided into two equal groups. Group I consisted of 30 patients receiving LA alone and undergoing simple extraction minor oral surgery, group II 30 patients receiving LA with oral midazolam and undergoing simple extraction or minor oral surgery. Results. There was a decrease in SaO2 from the baseline in 10% of group I patients, represented in 3 patients, 2 of them asthmatic and one anxious patient who the BP and HR raised slightly during LA admiration. There was a fall in SaO2 from the baseline in 53% of patients in group II, represented in 16 patients, the majority of them asthmatic and anxious patients, 6 patients with history of ischemic heart disease. The majority of these decreases in SaO2 or raining in BP or HR were associated with breath holding, in response to fear or emotional stress, during administration of LA due to vasoconstrictor effect or during elevation of teeth. The patients in group II showed a significantly (P<0. 001) greater maximum decrease in SaO2 from the baseline value compared to group I. The length of the operating time was longer in group II than that in group I, and the patients of group II were more anxious than the patients in group I. Conclusion. It was concluded that during simple extraction and minor oral surgery under LA alone or in combination with sedation procedures such as elevation of the tooth or administration of the LA may as a result of Breath holding cause reduction in SaO2 or raising in BP or HR. In fit patients this may be of little consequence, however patients with existing airway disease or Medically compromised patients may suffer significant falls in SaO2 or alter the Blood Pressure and Heart Rate. Therefor Monitoring of vital signs and oxygen saturation recommended during simple extraction dental surgery procedure and sedation as premedication for cardiac patients would be recommended. Citation: Hilal M, Ajanan N. Oxygen Saturation During Dental Surgery with Local Anaesthesia Alone and in Combination with Sedation in Medically Compromised Patients. Khalij-Libya J Dent Med Res. 2022;6(2):109–116. https://doi.org/10.47705/kjdmr.226203